Making the case that episodic recollection is attributable to operations occurring at retrieval rather than to content stored in a dedicated subsystem of long-term memory - Klein, Stan (Frontiers in Behavioral Neuroscience, 2013)
Episodic memory often is conceptualized as a uniquely human system of long-term memory that makes available knowledge accompanied by the temporal and spatial context in which that knowledge was acquired. Retrieval from episodic memory entails a form of first–person subjectivity called autonoetic consciousness that provides a sense that a recollection was something that took place in the experiencer’s personal past. In this paper I expand on this definition of episodic memory. Specifically, I suggest that (a) the core features assumed unique to episodic memory are shared by semantic memory, (b) episodic memory cannot be fully understood unless one appreciates that episodic recollection requires the coordinated function of a number of distinct, yet interacting, “enabling” systems. Although these systems – ownership, self, subjective temporality, and agency – are not traditionally viewed as memorial in nature, each is necessary for episodic recollection and jointly they may be sufficient, and (c) the type of subjective awareness provided by episodic recollection (autonoetic) is relational rather than intrinsic – i.e., it can be lost in certain patient populations, thus rendering episodic memory content indistinguishable from the content of semantic long-term memory.